2008
DOI: 10.1353/hpu.0.0032
|View full text |Cite
|
Sign up to set email alerts
|

Problem-solving Treatment for Depression among Mexican Americans in Primary Care

Abstract: The need to identify and improve access to evidence-based treatments for depressive disorders and other mental health problems is a public health priority, particularly in relation to racial/ethnic minorities and other underserved groups. One hundred forty-six Mexican American primary care patients who met diagnostic criteria for major depressive disorder, dysthymic disorder, or depressive disorder not otherwise specified (NOS) were offered eight sessions of an evidence-based behavioral treatment, problem-solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Of the 15 studies, nine were quantitative [51-54,56,57,60,63,64], five employed mixed methods [50,55,58,59,62] and one case study presented qualitative data [61]. Nine studies reported on culturally sensitive/culturally adapted psychological treatments (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 15 studies, nine were quantitative [51-54,56,57,60,63,64], five employed mixed methods [50,55,58,59,62] and one case study presented qualitative data [61]. Nine studies reported on culturally sensitive/culturally adapted psychological treatments (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The major ethnic groups represented in the studies were Latino immigrants living in the United States (US) (53.3%) [51,54-58,60,62] followed by Chinese-American immigrants (33.3%) [50,61,63,64]. The remaining studies focused on Chinese-Australians (7.1%) [53], Korean-Americans (6.7%) [52] and Turkish immigrants living in Austria (6.7%) [59].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations